2014
DOI: 10.1073/pnas.1407792111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and functional analysis of leukemic transformation of myeloproliferative neoplasms

Abstract: Patients with myeloproliferative neoplasms (MPNs) are at significant, cumulative risk of leukemic transformation to acute myeloid leukemia (AML), which is associated with adverse clinical outcome and resistance to standard AML therapies. We performed genomic profiling of post-MPN AML samples; these studies demonstrate somatic tumor protein 53 (TP53) mutations are common in JAK2V617F-mutant, post-MPN AML but not in chronic-phase MPN and lead to clonal dominance of JAK2V617F/TP53-mutant leukemic cells. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
278
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(303 citation statements)
references
References 35 publications
12
278
2
Order By: Relevance
“…The pathogenetic role of these other mutations is incompletely understood and might include cooperation with the driver mutations in facilitating disease progression [49,50]. Specific genes affected in this regard include those relevant to epigenetic (e.g., ASXL1, TET2, EZH2, IDH1, IDH2, DNMT3A), RNA splicing (e.g., SRSF2, U2AF1, SF3B1) or transcriptional (TP53, IKZF1, NF-E2, CUX1) regulation.…”
Section: Pathogenetic Contribution Of Mutations In Myeloproliferativementioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenetic role of these other mutations is incompletely understood and might include cooperation with the driver mutations in facilitating disease progression [49,50]. Specific genes affected in this regard include those relevant to epigenetic (e.g., ASXL1, TET2, EZH2, IDH1, IDH2, DNMT3A), RNA splicing (e.g., SRSF2, U2AF1, SF3B1) or transcriptional (TP53, IKZF1, NF-E2, CUX1) regulation.…”
Section: Pathogenetic Contribution Of Mutations In Myeloproliferativementioning
confidence: 99%
“…Mutations other than JAK2, CALR or MPL, which have been shown to have prognostic relevance in PMF, include ASXL1, SRSF2, EZH2, IDH1/2, and U2AF1 [51,52]. In addition, TP53, IDH2, SRSF2, and SH2B3 mutations have been reported to be over-represented in blastphase MPN, suggesting their relevance in disease progression [48,50,53]. Most noteworthy in this regard is TP53 loss, which is believed to make JAK2-mutated patients vulnerable to leukemic transformation [48,50].…”
Section: Pathogenetic Contribution Of Mutations In Myeloproliferativementioning
confidence: 99%
“…[19][20][21] The prognosis of MPN patients has been found to be dependent on the presence and the number of some of these additional mutations, such as ASXL1, SRSF2, IDH1, or IDH2, 22,23 whereas TP53 mutations are highly correlated to the development of acute transformation. 21,24,25 Interestingly, particular combinations of mutations could better define subgroups of patients with different outcomes. 26 Such molecular complexity could also affect the response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 A parallel could also be made with the overexpression of Jak2V617F in p53 2/2 mice, which induces leukemia. 9 Zhang et al observed a major increase in MPPs and MPs in Nras G12D p53 2/2 compared with controls. Importantly, these MPs displayed higher replating efficacy, and the transplantation of 10 000 MPs led exclusively to AML (as opposed to MPPs that led to both AML and T-ALL) in half of the animals, suggesting that they contain the LIC.…”
Section: Lic Licmentioning
confidence: 95%
“…8,9 Although orbital radiation is usually welltolerated, long-term complications, such as premature cataract and dryness, are dosedependent-and exceeding 36 Gy may increase risks of ischemic retinopathy, optic atrophy, corneal ulceration, and neovascular glaucoma. RT of orbital MZL rarely needs to exceed 30 Gy, and I hope that the readers of the University of Miami study will not conclude that the higher the orbital RT dose, the better.…”
mentioning
confidence: 99%